2013
DOI: 10.3390/w5041699
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater Tank Performance: Design and Management Criteria for Capture Tanks Using a Continuous Simulation and a Semi-Probabilistic Analytical Approach

Abstract: Stormwater tank performance significantly depends on management practices. This paper proposes a procedure to assess tank efficiency in terms of volume and pollutant concentration using four different capture tank management protocols. The comparison of the efficiency results reveals that, as expected, a combined bypass-stormwater tank system achieves better results than a tank alone. The management practices tested for the tank-only systems provide notably different efficiency results. The practice of immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The additional effect is that the collected rainwater is used, which means that demand on other water sources can be reduced . The question of runoff quality is also pertinent in urban areas, because the washing of impermeable pavements after rainfall events may bring considerable amounts of suspended pollutants into sewer systems (De Paola and De Martino, 2013). In a study carried out on the Tyrrhenian coastside of Italy, De Paola and Ranucci (2013) demonstrated the performance of a storm water capture tank in reducing TSS concentration in discharges from a sewer system serving a typical urban catchment.…”
Section: The Role Of Environment In Rainwater Harvestingmentioning
confidence: 99%
“…The additional effect is that the collected rainwater is used, which means that demand on other water sources can be reduced . The question of runoff quality is also pertinent in urban areas, because the washing of impermeable pavements after rainfall events may bring considerable amounts of suspended pollutants into sewer systems (De Paola and De Martino, 2013). In a study carried out on the Tyrrhenian coastside of Italy, De Paola and Ranucci (2013) demonstrated the performance of a storm water capture tank in reducing TSS concentration in discharges from a sewer system serving a typical urban catchment.…”
Section: The Role Of Environment In Rainwater Harvestingmentioning
confidence: 99%
“…On the other hand, each tank type can have different management rules, such as providing a bypass tank system or varying the emptying mode. This feature influences the efficiency of the system in terms of both pollutant mass and water volume discharged to the receiver [8]. Even so, Calabrò and Viviani (2006) [9] illustrated that storage tanks efficiently reduce the total suspended solids (TSS) discharged into a receiver.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall generators are commonly used in scientific studies [60,98,186]. Obtained data are employed for simulating the operation of sewerage networks including the volume of stormwater flooding [193,195], capacity of retention tanks [89,196], and as the volume and number of discharges through combined sewer overflow structures [98,[196][197][198].…”
Section: Data For Optimizationmentioning
confidence: 99%